Evaluation of Antitumor Activity of Valproic Acid on K562 cells: In Vitro - Shahin Aalaei Diman; Mehdi Mohamadzade; Yaghub Pazhang (Fasa University of Medical Sciences, 2016)
Backgrond & Objective: This study was performed to evaluate the antitumor effects of valproic acid (VPA) drug on K562 cells in vitro. Material & Methods: For this purpose, K562 cells were cultured and treated with different doses of valproic acid, and its antitumor properties were measured by MTT assay 24, 48, and 72 hours after treatment. Then, DNA electrophoresis and staining with Hoechst were used to analyze apoptotic cells in vitro. Results: The antitumor effects of valproic acid increased in a dose- and time- dependent manner. Also, the apoptotic effects of the drug were approved by electrophoresis. The maximum inhibitory effect was observed in higher concentration and after 72 hours treatment. IC50 was calculated 80Mµ by Compusyn software. The results showed that valproic acid was an efficient drug for inhibiting K562 cells, and its antitumoric effect would warrant further. Conclusion: Accordingly, valproic acid is suitable for inhibiting K562 cells, and these antitumoric properties would warrant further studies on the clinical application of valproic acid. Therefore, this drug might be effective for the prevention and treatment of chronic myeloid leukemia.